2009
DOI: 10.1186/gb-2009-10-2-r22
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread evidence for horizontal transfer of transposable elements across Drosophila genomes

Abstract: A genome-wide comparison of transposable elements reveals evidence for unexpectedly high rates of horizontal transfer between three species of Drosophila

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 70 publications
(81 reference statements)
7
165
1
Order By: Relevance
“…We identified clades of related insect species for which this situation may happen, by relying on the common assumption that inherited TEs evolve neutrally and similarly to synonymous sites of protein coding genes (20). This assumption implies that TEs showing higher interspecific homology than the synonymous sites of orthologous genes should share a more recent ancestor than the host species, and hence be the result of HT (16,21). Conversely,…”
Section: Resultsmentioning
confidence: 99%
“…We identified clades of related insect species for which this situation may happen, by relying on the common assumption that inherited TEs evolve neutrally and similarly to synonymous sites of protein coding genes (20). This assumption implies that TEs showing higher interspecific homology than the synonymous sites of orthologous genes should share a more recent ancestor than the host species, and hence be the result of HT (16,21). Conversely,…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that poxviruses have vectored retroposons between reptiles and mammals, and members of four DNA TE families are found in both vertebrates and blood-sucking triatomid bugs, suggesting possible mechanisms for intertaxon transfers. A study in Drosophila genomes finds that approximately one-third of TE families originated from recent interspecies lateral transfers, with an estimated transfer rate of 0.04 events per family per million years (30). In fact, lateral movement across host taxa is believed to be an important mechanism for long-term maintenance of TE families.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%
“…Third, sequences that are not annotated in Flybase but had some limited sequence identity with ZAM and Tirant fragments correspond in fact to a newly identified element that we named Agoriino and a Pifo element. Pifo was previously identified in Drosophila yakuba (20) and a 4,414-bp degenerate Pifo in D. melanogaster (21). Consequently, only one vestige of ZAM is present at position X:21649838..21655021.…”
Section: In Silico Analysis Of the Flam Locus Reveals A Large Number mentioning
confidence: 99%
“…Bartolomé et al (20) suggested that one-third of the TE families originated from recent horizontal transfer between D. melanogaster, D. simulans, and D. yakuba. Our data reveal that this rate is even higher in flam, reaching two-third of the recent elements.…”
Section: Structural Modifications Affecting Flam May Explain Differenmentioning
confidence: 99%